The role of zakat towards poverty reduction : an analytical study from the contemporary tafasir - Habibullah, Mohammad (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The purpose of this study is to provide a general exposition on the concept and management of zakat, in particular applying it to poverty reduction as an important panacea in today's widespread situation of financial calamity. The objectives of this research is to analyze the implication of zakat on poverty reduction as it is an obligatory ibadah to perform by every wealthy Muslim. The other objective of this study is to find the theoretical and practical basis of poverty reduction by analyzing the Qur'anic verses from the opinion of Mufassiran. Therefore, the researcher attempts to investigate the failure of zakat management and distribution or any other factors that may have caused its inability to realize its objective towards poverty reduction. The main objective of zakat revenue is to fulfil the basic needs, especially to help the poor and the needy, in addition to other generous sources in the society. Zakat giving and its good governance will greatly complement and supplement socio-economic justice leading towards poverty reduction. The collection and distribution of zakat complement the Islamic doctrine of socioeconomic neutrality, which is incorporated in the responsibilities of the authorities who are entrusted to lessen poverty. This refers to ability to fulfil basic needs such as food, shelter, education and health. In Islam, poverty is assumed to have been eradicated when the basic needs are fulfilled and minimum level of living for everyone has been satisfied. Thus, to eradicate poverty is to satisfy the basic needs of life which are relative in nature. The outcomes of this research is that the Zakat can be added to consumption demand in the economy by redistributing income from the rich to the poor. It can also be encouraged investment by checking the tendency to hoard idle money, and adding to the production of goods and services of common use for the poor. Thus, Zakat financed projects in the fields of education, medical care and social welfare will increase the productivity of the poor. The methods of data collection involved library research through reading and content analysis of primary and secondary sources. The process of poverty reduction has been discussed in the Qur'an and Sunnah in different ways.